Investigating molecular junctions based on mixed self-assembled monolayers to understand the impact of intermolecular interactions on transport - Feng, Jiajun; Bâldea, Ioan; Gao, Jiajie; Jeong, Gookyeong; Frisbie, C. Daniel; Xie, Zuoti (ACS nano, 2024)
To interrogate the importance of intermolecular interactions on charge transport at the nanoscale, we investigate molecular tunnel junctions based on mixed self-assembled monolayers (SAMs) of 1-alkyl (CnT) thiols and their fluorinated counterparts (F-CnT) that have substantially different tunneling conductances. Experiments on mixed CnT1-x:F-CnTx SAMs between Au contacts reveal a strongly nonlinear (exponential) dependence of the tunneling conductance G on composition x, a behavior that is tempting to assign to the strong impact of intra-SAM intermolecular interactions. However, analysis suggests that the exponential dependence of G on x does not arise from intra-SAM intermolecular interactions, but instead emerges from the work function modification of the Au electrode which varies linearly with x.
Online veröffentlicht: 6. November 2024
Gesehen am 23.07.2025